73‐3: Super Multi‐View 3D Display with Reduced Accommodation‐Vergence Conflict using the Holographic Method. Issue 1 (May 2016) - Song, Hoon; Seo, Wontaek; An, Jungkwuen; Seo, Juwon; Sung, Geeyoung; Choi, Chil-Sung; Kim, Sunil; Kim, Hojung; Kim, Yunhee; Kim, Yun-Tae; Kim, Young; Kim, Yongkyu; et al.
Abstract : Novel 3D display architecture and algorithm are proposed and demonstrated Full HD 3D image with reduced accommodation‐vergence conflict using limited computing power and a conventional LCD panel. The proposed 3D display architecture is integrated with a commercial 5.5" Full HD LCD panel and the used algorithm needs remarkably lower computing power than a conventional CGH algorithm based on Fresnel transformation. The experimental results show the accommodation depth cue which provides a clear 3D image only on focus position.